2007
DOI: 10.1063/1.2719668
|View full text |Cite
|
Sign up to set email alerts
|

Double and triple junction polymer solar cells processed from solution

Abstract: Multiple junction solar cells incorporating polymer:fullerene bulk heterojunctions as active layers and solution processed electron and hole transport layers are presented. The recombination layer, deposited between the active layers, is fabricated by spin coating ZnO nanoparticles from acetone, followed by spin coating neutral pH poly(3,4-ethylenedioxythiophene) from water and short UV illumination of the completed device. The key advantage of this procedure is that each step does not affect the integrity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
290
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 344 publications
(298 citation statements)
references
References 26 publications
7
290
1
Order By: Relevance
“…However, the narrow absorption properties combined with low charge carrier mobilities limit the performance of the organic solar cells [1,2]. One way to improve the absorption of organic solar cells is by using tandem (or multi-junction) structures [3][4][5][6][7][8][9][10]. Because of the different band gap of the active layer each sub cell then absorbs light in a different part of the solar spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…However, the narrow absorption properties combined with low charge carrier mobilities limit the performance of the organic solar cells [1,2]. One way to improve the absorption of organic solar cells is by using tandem (or multi-junction) structures [3][4][5][6][7][8][9][10]. Because of the different band gap of the active layer each sub cell then absorbs light in a different part of the solar spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Most tandem cells reported so far, have the traditional polarity confi guration, that is, with a transparent hole collecting contact and an opaque metallic electron collecting contact. However, inverted confi gurations with a metallic hole-collecting contact and transparent electron-collecting contact [ 10 , 11 ] may have an advantage with respect to printability and stability due to the relative environmental stability of the electron transport layer and hole-collecting contact.…”
mentioning
confidence: 99%
“…103 Recently, Gilot et al reported solution-processable ZnO NPs as the recombination layer, which paved the path for an all-solution processed tandem devices. 96 Recently, Yang et al reported a tandem solar cell with efficiency approaching 7.0% using modified PEDOT:PSS as an interconnecting layer. 20 Interestingly, Heeger et al reported tandem solar cells and evaluated the robustness of the system using PCPDTBT/PCBM and poly(3-hexylthiophene)/PCBM as active layers for the two cells, and a sol-gel processed TiOx as the recombination layer.…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
“…Tandem cells were originally developed by Hiramoto et al, 101 and since then, both vacuum-deposited 102 and solution-processed 96 active layers have been used to fabricate tandem devices. However, semitransparent thin-layer of metal that were used as the recombination layer in these devices led to optical losses.…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation